Politik Protes dan Etnisitas: Kasus Buruh Cina di Tambang Timah di Bangka-Belitung (1920-1950) - Erwiza Erman (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
The history of Chinese society during the New Order government was so politically sensitive and economically played an important role. However, during the development of the national history of Indonesia, the fate of ethnic minorities turned out rather as people without history , devoid of any important role in the history of the nation. By conducting a case study in the islands of Bangka-Belitung, this article tries to reveal the history of the lower classes of society who become tin miners. The article analyses the relationship between ethnicity and the political protest of the tin miners by placing it in the context of the regime change of 1920 - 1950. This article shows that at a certain time, the relation between political protest and ethnic consciousness overlapped with class consciousness. At other times, political protest is no longer solely caused by ethnic consciousness, but rather colored by class consciousness.Keywords: political protest, etnicity, Chinese tin miners, Bangka-Belitung